KEHIDUPAN KOMUNITAS PUNK DI KOTA PASIR PANGARAIAN - Monita, Septia; ", Syafrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Punk is a culture that was born in the country of England. Assessment of Punk in looking at a problem can be seen through the lyrics of the song that tells about the problems of political, environmental, economic, ideological, social and even religious problem. The Punk community in Pasir Pangaraian is a group of people who run the activities of life with their togetherness based on the principle of voluntary cooperation with the cultural lifestyle of Western countries with their fashion show. This research aims to find out what factors aspects influenced the Punk community into a teenager and to analyze patterns of community life in the city's Punk Pasir Pangaraian. This research collected through observation and interview method documentation. The analysis by using a descriptive qualitative analysis. The results of this research it can be concluded that the factor behind their teens become the Punk community are, among others: (1) the family of the problems of lack of attention and affection of a family especially the elderly. (2) the height of the Punk community members such as solidarity, a sense of community, a sense of the importance of unity, a sense of sympathy, concern for friends and mutual help to each other. (3) the influence of friends became one of the factors that cause a person to become a member of the Punk community, choose call buddy who overall has affected the mindset of the individual. (4) the economic Problem also affects individual families to find new life as lived a life as members of the Punk community. Furthermore the Punk community life patterns in the Pasir Pangaraian can be seen from the variety of activities they do in the morning, afternoon, and evening.Keywords: Punk community, Patterns of life